Pengaruh Jenis Kemasan Dan Lama Penyimpanan Terhadap Karakteristik Mutu Buah Harimonting ( Rhodomytus Tomentosa) - Hotman Manurung; Rosnawyta Simanjuntak (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2019)
The purpose of this study was to determine the effect of the type of packaging on characteristics of quality of the karimunting fruits during storage. The experimental design used was completely randomized design with two factors. The first factor was type of packaging with 2 levels, namely polyethylene (PE) plastic box and wrapping packaging. The second factor was storage duration (L): 0, 1, 2, 3, and 4 days. The study was conducted with 3 replications. Parameters observed were IC50, weight loss, texture, color, total soluble solid, and color preference. The results showed that the longer storage the higher IC50 for both PE and wrapping. The highest IC50 (97.04 ppm) was in the storage of day 4 with PE plastic packaging. The reduction of weight was higher with plastic packaging (7.40%) compared with wrapping packaging (4.80%). Karimunting packed with PE plastic produced higher total solid soluble (TSS) (7.60brix) compared with wrapping storage (6.20brix)